ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP BELAJAR MAHASISWA PROGRAM STUDI EKONOMI SYARIAH UNIVERSITAS ISLAM IBRAHIMY BANYUWANGI - Pamungkas, Syehnur Bongkar; Imawan, Riswanda; Izza, Rohma Nur; Virtiani, Vita (Department of Sharia Economics, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2025)
There are differences between students who take part in organizations and those who do not. Organizational culture is a shared value shared by all members of the organization within it. In its characteristics, organizational culture can be said to be what is perceived by students and the way that perception will give rise to a certain pattern of values, beliefs and views. Basically, learning is a process of change in the human personality and this change is manifested in the form of increasing the quality and quantity of behavior such as increasing effectiveness, responsibility, discipline and initiative. Even though this difference is not very strong, it makes researchers interested in conducting this research. In this research the author used a quantitative research approach method. Based on the results of the T Test research, organizational culture variables have a partial influence on the learning of students in the Sharia Economics Study Program, Ibrahimy Banyuwangi Islamic University with a significance value of 0.000, less than 0.05 with an influence of 0.800. This can be interpreted as meaning that organizational culture has a contributing impact on the learning of students in the Sharia Economics Study Program at the Ibrahimy Islamic University, Banyuwangi.